Reduction of foodborne pathogens during cattle manure composting with addition of calcium cyanamide - Simujide, Huasai; Aorigele, Chen; Wang, Chun-Jie; Manda, Bai; Lina, Ma; Wu, Mei-Yun; Li, Yu; Bai, Tong-Ri-Ge (Journal of Environmental Engineering and Landscape Management, 2013)
Inactivation of four species of foodborne pathogens (E. coli, Salmonella, E. faecalis, and S. aureus) was investigated during laboratory-scale composting of fresh cow manure with addition of calcium cyanamide (CaCN2) at constant temperature conditions, and the effects of temperature and additive content of CaCN2 on the efficacy of inactivation were evaluated. At different composting temperatures (20, 30, 37 and 50 °C), a significant inhibition or quick inactivation of pathogens were observed during 10 d composting with addition of 2.0% CaCN2, and the effect was more obvious at mesophilic temperatures compared to thermophilic temperature. Therefore, the ideal additive content of CaCN2 was determined at 30 °C through mixing 2.0%, 2.5%, and 3.0% CaCN2 with manure. With increase in additive content of CaCN2, the efficacies of pathogen inactivation also increased. However, the result indicates that, no less than 2.5% CaCN2 should be mixed with the manure to entirely eliminate the pathogens during composting.